Fluctuations and the axial anomaly with three quark flavors - Mitter, Mario; Schaefer, Bernd-Jochen (Physical review. D, Particles, fields, gravitation, and cosmology, 2014)
The role of the axial anomaly in the chiral phase transition at finite temperature and quark chemical potential is investigated within a nonperturbative functional renormalization group approach. The flow equation for the grand potential is solved to leading order in a derivative expansion of a three-flavor quark-meson model truncation. The results are compared with a standard and an extended mean-field analysis, which facilitates the exploration of the influence of bosonic and fermionic fluctuations, respectively, on the phase transition. The influence of U(1)A-symmetry breaking on the chiral transition, the location of a possible critical end point in the phase diagram and the quark mass sensitivity are studied in detail.